ER subtype selectivity of m-carborane-containing phenols: C-alkyl groups on the m-carborane cage enhance ERα selectivity. Issue 16 (15th August 2019) - Ohta, Kiminori; Ogawa, Takumi; Kato, Koichi; Oda, Akifumi; Endo, Yasuyuki
Graphical abstract: Abstract: Estrogen receptor (ER) exhibits two subtypes, ERα and ERβ, whose biological functions are quite different despite expression in the same tissues. We developed diiodo-m-carborane derivative 3a, which showed 14-fold selectivity for ERβ with high binding affinity toward ERβ. Interestingly, introduction of an alkyl group into the carbon atom of the m-carborane cage of 3a markedly enhanced the binding affinity toward ERα and decreased affinity toward ERβ. C- n -propyl derivative 3d showed 28-fold selectivity for ERα in an ER binding assay and promoted proliferation of MCF-7 breast cancer cells. Docking simulation studies suggest that the directions of the n -propyl group and the diiodo substituent introduced on the m-carborane cage play important roles for the control of ER subtype selectivity. As 3a and 3d showed ERβ and ERα selectivity with high binding affinity, respectively, these ligands may be useful as biological tools to aid in understanding the different roles of ER subtypes.